Historical Changes and Future Trends of Extreme Precipitation and High Temperature in China - Shu Zhangkang; 2; 3; 4; Li Wenxin; 3; 4; Zhang Jianyun; 3; 4; Jin Junliang; 3; et al. (中国工程科学, 2022)
Extreme events occur frequently in China against the background of global warming. Understanding the spatiotemporal variation of extreme events and predicting their future trends can provide a theoretical basis for formulating regional strategies that adapt to climate change. Using the CN05.1 grid meteorological data and eleven global climate models based on Coupled Model Intercomparison Project Phase 6 (CMIP6), we analyzed the evolution characteristics of extreme precipitation and high temperature events in China from 1975 to 2014, predicted the evolution of extreme events from 2015 to 2054, and proposes policy suggestions for dealing with these events. The results indicate that, from 1975 to 2014, the heavy precipitation exhibited an increasing-decreasing-increasing pattern from the northwest to southeast region of China, and the risk and catastrophability of extreme precipitation in regions located to the east of the Hu Line were great. Under SSP1-2.6 and SSP5-8.5 climate change scenarios, extreme precipitation in China will generally increase and become stronger by 2054, with a significant increase in North and Northeast China and a further increase in Northwest China. From 1975 to 2014, the number of warm nights and warm days in China increased significantly, and the increase in warm nights was higher than that of warm days. Under the SSP1-2.6 and SSP5-8.5 climate change scenarios, extreme heat events in China will increase significantly by 2054, with the greatest increase in Northwest, Southwest, and South China. To mitigate the impact of climate change and cope with the risk of extreme events in the future, China should further improve its response and emergency management capacities for dealing with flood and extreme heat risks, strengthen international cooperation, and formulate strategies adapted to local conditions.